Effects of In Utero Exposure to Ethinyl Estradiol on Tamoxifen Resistance and Breast Cancer Recurrence in a Preclinical Model. (8th September 2016) - Hilakivi-Clarke, Leena; Wärri, Anni; Bouker, Kerrie B; Zhang, Xiyuan; Cook, Katherine L; Jin, Lu; Zwart, Alan; Nguyen, Nguyen; Hu, Rong; Cruz, M Idalia; de Assis, Sonia; Wang, Xiao; et al.
Abstract : Background: Responses to endocrine therapies vary among patients with estrogen receptor (ER+) breast cancer. We studied whether in utero exposure to endocrine-disrupting compounds might explain these variations. Methods: We describe a novel ER+ breast cancer model to study de novo and acquired tamoxifen (TAM) resistance. Pregnant Sprague Dawley rats were exposed to 0 or 0.1 ppm ethinyl estradiol (EE2), and the response of 9, 12-dimethylbenz[a]anthracene (DMBA)-induced mammary tumors to 15 mg/kg TAM, with (n = 17 tumors in the controls and n = 20 tumors in EE2 offspring) or without 1.2 g/kg valproic acid and 5 mg/kg hydralazine (n = 24 tumors in the controls and n = 32 tumors in EE2 offspring) in the female offspring, was assessed. One-sided Chi2 tests were used to calculate P values. Comparisons of differentially expressed genes between mammary tumors in in utero EE2-exposed and control rats, and between anti-estrogen-resistant LCC9 and -sensitive LCC1 human breast cancer cells, were also performed. Results: In our preclinical model, 54.2% of mammary tumors in the control rats exhibited a complete response to TAM, of which 23.1% acquired resistance with continued anti-estrogen treatment and recurred. Mammary tumors in the EE2 offspring were statistically significantly less likely to respond to TAM ( P = .047) and recur ( P = .007). In the EE2 offspring, but not in controls, adding valproic acid and hydralazine to TAM prevented recurrence ( P < .001). Three downregulated and hypermethylated genes (KLF4, LGALS3, MICB) and one upregulated gene (ETV4) were identified in EE2 tumors and LCC9 breast cancer cells, and valproic acid and hydralazine normalized the altered expression of all four genes. Conclusions: Resistance to TAM may be preprogrammed by in utero exposure to high estrogen levels and mediated through reversible epigenetic alterations in genes associated with epithelial-mesenchymal transition and tumor immune responses.